Constructing zigzag-like hollow mesoporous nanospheres MoO2/C with superior lithium storage performance. (7th January 2022) - Zhao, Wencai; Yuan, Yongfeng; Yin, Simin; Cai, Gaoshen; Guo, Shaoyi
Abstract: Hollow mesoporous nanospheres MoO2 /C are successfully constructed through metal chelating reaction between molybdenum acetylacetone and glycerol as well as the Kirkendall effect induced by diammonium hydrogen phosphate. MoO2 nanoparticles coupled by amorphous carbon are assembled to unique zigzag-like hollow mesoporous nanosphere with large specific surface area of 147.7 m 2 g −1 and main pore size of 8.7 nm. The content of carbon is 9.1%. As anode material for lithium-ion batteries, the composite shows high specific capacity and excellent cycling performance. At 0.2 A g −1, average discharge capacity stabilizes at 1092 mAh g −1 . At 1 A g −1 after 700 cycles, the discharge capacity still reaches 512 mAh g −1 . Impressively, the composite preserves intact after 700 cycles. Even at 5 A g −1, the discharge capacity can reach 321 mAh g −1, exhibiting superior rate capability. Various kinetics analyses demonstrate that in electrochemical reaction, the proportion of the surface capacitive effect is higher, and the composite has relatively high diffusion coefficient of Li ions and fast faradic reaction kinetics. Excellent lithium storge performance is attributed to the synergistic effect of zigzag-like hollow mesoporous nanosphere and amorphous carbon, which improves reaction kinetics, structure stability and electronic conductivity of MoO2 . The present work provides a new useful structure design strategy for advanced energy storage application of MoO2 .